Spatiotemporal Variation in Precipitation and Water Vapor Transport Over Central Asia in Winter and Summer Under Global Warming - Yang, Hao; Xu, Guanyu; Mao, Haixiang; Wang, Yan (Frontiers in Earth Science, 2020)
Under the background of global warming, the studies of quantitative water vapor transport characteristics in arid and semi-arid Central Asia are rare. We examine the spatiotemporal variation of precipitation in Central Asia from 1979 to 2017 based on Global Precipitation Climatology Project (GPCP) and circulation reanalysis data. We simulate the sources and transport of water vapor in different regions of Central Asia in winter and summer using the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model. The seasonal variation in precipitation over the whole region of Central Asia shows a single minimum in September, with little change in the amount of precipitation in other months; however, there are clear regional and seasonal differences in precipitation in western (region I) and eastern (region II) Central Asia. In region I, the maximum and minimum amounts of precipitation are observed in winter and summer, respectively, whereas in region II, the maximum amount of precipitation occurs in summer and the minimum in winter. The amount of precipitation in winter increased significantly more than the amount of precipitation in summer in both regions I and II from 1979 to 2017. Quantitative calculations of water vapor transport show that Europe and the North Atlantic Ocean are the largest sources of water vapor for regions I and II and contribute >50% of the transport of water vapor in both winter and summer. The contribution of water vapor from other sources varies greatly in different seasons. For region I, the second highest contribution to water vapor in winter is transport from the South Atlantic Ocean, while in summer is from the Arctic Ocean and northern Asia. For region II, water vapor from the local area (Xinjiang) makes an important contribution in summer. In summer, the northerly currents from the Arctic Ocean are strong due to the anticyclonic circulation maintained in Central Asia. The water vapor flux budget across each border and the net budget in region I are higher than those in region II in winter. The response of water vapor transport to global warming in Central Asia shows a north shift during past 40 years.